2017
DOI: 10.3390/nu9050474
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Recruitment, Adherence and Drop-Out Rates in Omega-3 Polyunsaturated Fatty Acid Supplementation Trials in Children and Adolescents

Abstract: Introduction: The influence of n-3 long-chain polyunsaturated fatty acids (n-3 LCPUFA) supplementation on health outcomes has been studied extensively with randomized controlled trials (RCT). In many research fields, difficulties with recruitment, adherence and high drop-out rates have been reported. However, what is unknown is how common these problems are in n-3 LCPUFA supplementation studies in children and adolescents. Therefore, this paper will review n-3 LCPUFA supplementation studies in children and ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 167 publications
1
11
0
Order By: Relevance
“…Also note that the recruitment rate (i.e., percentage of those invited who decided to participate) was approximately 13%, this could limit the external validity. However, such recruitment rate is rather common in a school setting [ 95 ]. Moreover, this was a cross-sectional study and can thus not be used for proving causal relationships, experimental studies are needed for more insight in the effects of fatty acids in depression and self-esteem in this specific target group.…”
Section: Discussionmentioning
confidence: 99%
“…Also note that the recruitment rate (i.e., percentage of those invited who decided to participate) was approximately 13%, this could limit the external validity. However, such recruitment rate is rather common in a school setting [ 95 ]. Moreover, this was a cross-sectional study and can thus not be used for proving causal relationships, experimental studies are needed for more insight in the effects of fatty acids in depression and self-esteem in this specific target group.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the students had to take eight capsules per day, which many students indicated to be too much and was another reason why many students dropped-out (inability to take capsules). Long study duration and high number of capsules have been suggested to influence drop-out and adherence [73]. It is however important to realize that if n-3 LCPUFA supplementation is found to be beneficial for depressive feelings, a high dose of capsules might need to be taken for a prolonged period of time (i.e., months or years).…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews and other studies of this question provide inconsistent results, as they include heterogeneous groups of participants, interventions, comparators and outcomes [ 10 , 11 , 16 20 ]. Furthermore, there are implementation differences in dose, delivery, uptake and context both generally [ 35 ], specifically to this field [ 36 ], and with regard to this trial as discussed (see above). Consequently, the ratio of true to no relationships in the area of fatty-acid supplementation is problematic, and this is partly due to the large number of small studies finding small effects which are known to provide a poor basis for replication.…”
Section: Discussionmentioning
confidence: 99%